Comparative Endocrinology of Animals - Narayan, Edward (IntechOpen, 2019)
In this book, the editor has reviewed the scientific articles from a diverse group of scientists from around the world who actively participate in comparative endocrinology. Some of the important categories represented here are human health, aquaculture, wildlife conservation, and production animals. Eminent scientists write from their experience, providing an overview of the current information on comparative endocrinology of animals. The chapters also provide valuable information for animal production and human health management. The book will be useful to biologists, biomedical researchers, veterinary students, wildlife managers, researchers, and wildlife conservationists.